Starch-coated hard carbon negative electrode material, preparation method thereof and sodium ion battery

The starch is crosslinked and modified in situ by a starch modifier to make it evenly adhere to the hard carbon surface. Combined with the secondary carbonization and screening steps, a starch-coated hard carbon negative electrode material with excellent electrochemical performance was prepared, which solved the problem of low performance caused by the porous structure of the hard carbon negative electrode material and achieved efficient sodium ion battery negative electrode material.

CN119612490AActive Publication Date: 2025-03-14GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411789343.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In existing sodium ion batteries, the porous structure of hard carbon negative electrode material leads to a higher material ratio, low capacity and first-term efficiency, and the commonly used coating process is complex and costly, which limits large-scale production.

Method used

The starch is crosslinked and modified in situ by a starch modifier to make it adhere evenly to the hard char surface, improve the closed-pore structure and uniform distribution. The mixing and drying process of modified starch and hard char powder is adopted, combined with the secondary carbonization and screening steps, a starch-coated hard char negative electrode material with excellent electrochemical properties is prepared.

Benefits of technology

The specific surface area of ​​hard charcoal is significantly reduced, the efficiency and specific capacity of the first coulomb are improved, and the rate performance and cycle performance are improved. The first reversible specific capacity of 0.1C is increased by 10mAh/g~65mAh/g, the first coulomb efficiency is ≥90.1%, the proportion of the ratio capacity under 1C current is increased by 16.9% to 24.1%, and the capacity retention rate after 300 cycles at 0.5C is ≥98.8%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174935630000111
    Figure BDA0005174935630000111
  • Figure BDA0005174935630000121
    Figure BDA0005174935630000121
  • Figure BDA0005174935630000131
    Figure BDA0005174935630000131
Patent Text Reader

Abstract

The invention relates to the technical field of battery material preparation, and provides a starch-coated hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. The preparation method of the starch-coated hard carbon negative electrode material comprises the following steps: (1) carrying out pre-carbonization, crushing and primary carbonization on a hard carbon precursor to obtain hard carbon powder; (2) uniformly mixing the hard carbon powder and starch to obtain mixed powder, dissolving a starch modifier in a solvent to form a modified solution, reacting the modified solution with the mixed powder, and drying to obtain a modified precursor, the starch modifier comprising an amine organic matter and an ester organic matter; and (3) carrying out secondary carbonization on the modified precursor, and screening. The starch-coated hard carbon negative electrode material prepared by the invention has a reduced specific surface area and a proper closed-pore structure, has relatively high first coulombic efficiency and specific capacity when being used in a sodium ion battery, and can also effectively improve rate capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a starch-coated hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] In today's society that pursues new energy and carbon neutrality, electrochemical energy storage has become a global research focus. Sodium-ion batteries have the advantages of a wide range of raw material sources, low prices, good comprehensive performance, and are not limited by lithium resources. They are more in line with the needs of large-scale energy storage. Since sodium-ion batteries cannot form stable compounds with traditional lithium-ion battery graphite negative electrode materials during the charging and discharging process, ideal negative electrode materials have become one of the reasons restricting the development of sodium-ion batteries. Hard carbon is a carbon material that is difficult to graphitize above 2500°C. It has the advantages of high sodium storage capacity, stable potential, small volume deformation after sodium insertion, low temperature and good fast charging performance, making it the most ideal sodium negative electrode material.

[0003] At present, biomass, coal, resins, such as microcrystalline cellulose, rice husks, bituminous coal, and phenolic resins have been converted into a series of sodium ion battery starch-coated hard carbon negative electrode materials. However, due to the inherent complexity of the precursor caused by the coexistence of multiple components, during the carbonization process, these components decompose in some special ways at different temperatures and interact with each other, so that the hard carbon material forms a porous structure. This porous structure will lead to a high specific surface area of ​​the material, low capacity and initial efficiency, and low battery energy density. In order to enhance the application of hard carbon as a sodium ion negative electrode material, coating of hard carbon materials is currently an effective means. Commonly used coating methods include: vapor deposition method, hydrothermal method, and polymer coating, but these processes are relatively complex, with high production costs, complex processes, and low yields during the production process, which is not conducive to large-scale production and preparation. Summary of the invention

[0004] In view of the above problems, the object of the present invention is to provide a starch-coated hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. The starch-coated hard carbon negative electrode material prepared by the present invention has a reduced specific surface area and a suitable closed-pore structure, and has a higher first coulombic efficiency and specific capacity when used in a sodium ion battery, and can effectively improve the rate performance and cycle performance.

[0005] To achieve the above object, the first aspect of the present invention provides a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0006] (1) Pre-carbonizing, crushing, and once carbonizing a hard carbon precursor to obtain a hard carbon powder;

[0007] (2) mixing hard carbon powder and starch uniformly to obtain a mixed powder, dissolving a starch modifier in a solvent to form a modified solution, and then reacting the modified solution with the mixed powder and drying to obtain a modified precursor, wherein the starch modifier includes an amine organic substance and an ester organic substance;

[0008] (3) The modified precursor is subjected to secondary carbonization and screening.

[0009] Compared with the prior art, the present invention takes hard carbon material as the main body, and uses starch modifier to perform in-situ cross-linking modification on starch, so as to achieve uniform adhesion of starch to the hard carbon surface, improve the closed-pore structure and uniform distribution of starch-coated hard carbon negative electrode materials after carbonization, and improve the first coulombic efficiency and specific capacity. The starch modifier of the present invention includes amine organic matter and ester organic matter, wherein the amine organic matter can be grafted onto starch to improve its swelling property, so that the starch is more evenly coated on the hard carbon surface, and at the same time, the grafted nitrogen-containing functional groups will increase the content of pyridine and pyrrole nitrogen formed after carbonization, which can provide more electron transmission channels and more active sites, thereby increasing the conductivity and topological defects of starch-coated hard carbon negative electrode materials, and at the same time, the access of nitrogen-containing functional groups can change the atomic structure of the edge or bulk phase of graphite carbon, thereby improving the battery rate performance and cycle performance. The introduction of ester organic matter can form a binder with starch, increase the bonding force between starch and the main skeleton of hard carbon, provide more closed-pore structures, reduce the specific surface of hard carbon, and improve the first coulombic efficiency and specific capacity. Therefore, compared with the uncoated hard carbon powder, the starch-coated hard carbon negative electrode material prepared by the preparation method of the present invention has an increased first reversible specific capacity of 10 mAh / g to 65 mAh / g at 0.1C, an initial coulombic efficiency ≥ 90.1%, an increased rate capacity ratio at 1C current of 16.9% to 24.1%, and a capacity retention rate of ≥ 98.8% after 300 cycles at 0.5C.

[0010] In some embodiments, the hard carbon precursor is selected from at least one of biomass, coal and resin, and is pulverized in a jet mill. The particle size Dv 50 of the pulverized material is 3 μm to 8 μm, and the specific surface area is 10 m 2 / g~200m 2 / g.

[0011] In some embodiments, the pre-carbonization temperature is 400°C to 700°C, the pre-carbonization time is 0.5h to 10h, the primary carbonization temperature is 1100°C to 1600°C, and the primary carbonization insulation time is 0.5h to 10h.

[0012] In some embodiments, the pre-carbonization, the primary carbonization and the secondary carbonization are all performed in an inert atmosphere, and the inert atmosphere is independently selected from at least one of nitrogen and argon.

[0013] In some embodiments, the mass ratio of hard carbon powder to starch is 1:0.05-0.5, the mass ratio of amine organic matter, ester organic matter and solvent is 0.2-0.5:0.5-0.8:1.0-1.5, and the mass ratio of modified solution to mixed powder is 0.5-2:1.

[0014] In some embodiments, the starch is selected from at least one of wheat starch, corn starch and potato starch, the amine organic matter is selected from at least one of acrylamide, ethylenediamine and aniline, the ester organic matter is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate and dicyclohexylmethane diisocyanate, and the solvent is selected from at least one of petroleum ether, ethyl acetate, acetone and tetrahydrofuran.

[0015] In some embodiments, the reaction temperature is 50°C to 100°C, the reaction time is 1 h to 10 h, the drying temperature is 80°C to 250°C, and the drying time is greater than 5 h.

[0016] In some embodiments, the temperature of the secondary carbonization is 900° C. to 1400° C., the insulation time of the secondary carbonization is 0.5 h to 10 h, and the mesh size used for screening is 200 mesh to 400 mesh.

[0017] The second aspect of the present invention provides a starch-coated hard carbon negative electrode material, which is prepared by the aforementioned method for preparing the starch-coated hard carbon negative electrode material.

[0018] A third aspect of the present invention provides a sodium ion battery, comprising a positive electrode material and a negative electrode material, wherein the negative electrode material is the aforementioned starch-coated hard carbon negative electrode material. DETAILED DESCRIPTION

[0019] The present invention provides a sodium ion battery, comprising a positive electrode material and a negative electrode material. The positive electrode material comprises at least one of a sodium cobaltate positive electrode material, a sodium iron phosphate positive electrode material, a sodium nickel cobalt manganate positive electrode material, and a sodium nickel cobalt aluminum acid positive electrode material; the negative electrode material is a starch-coated hard carbon negative electrode material provided by the present invention, and the starch-coated hard carbon negative electrode material can be used alone or mixed with other negative electrode materials (such as expanded graphite, graphite intercalation compounds, and soft carbon, etc.). The preparation method of the starch-coated hard carbon negative electrode material of the present invention comprises the steps of:

[0020] (1) Pre-carbonizing, crushing, and once carbonizing a hard carbon precursor to obtain a hard carbon powder;

[0021] (2) mixing hard carbon powder and starch uniformly to obtain a mixed powder, dissolving a starch modifier in a solvent to form a modified solution, and then reacting the modified solution with the mixed powder and drying to obtain a modified precursor;

[0022] (3) The modified precursor is subjected to secondary carbonization and screening.

[0023] In step (1), the hard carbon precursor is selected from at least one of biomass, coal and resin. Specifically, the biomass can be selected from at least one of microcrystalline cellulose, wheat straw and rice husk; the coal can be selected from at least one of lignite, sub-bituminous coal, bituminous coal and anthracite; the resin can be selected from phenolic resin. In some technical schemes, the hard carbon precursor is selected from microcrystalline cellulose. In some technical schemes, the hard carbon precursor is selected from rice husk. In some technical schemes, the hard carbon precursor is selected from phenolic resin. In some technical schemes, the hard carbon precursor is selected from bituminous coal.

[0024] Pre-carbonization is carried out in an inert atmosphere, and the inert atmosphere is selected from at least one of nitrogen and argon. The temperature of pre-carbonization is 400°C to 700°C. In some technical schemes, the temperature of pre-carbonization is 420°C to 660°C. In some technical schemes, the temperature of pre-carbonization is 465°C to 645°C. As an example, the temperature of pre-carbonization can be, but is not limited to, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, and 700°C. The time of pre-carbonization is 0.5h to 10h. In some technical schemes, the time of pre-carbonization is 2h to 8h. As an example, the pre-carbonization time can be, but is not limited to, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h. The hard carbon precursor is pre-carbonized at 400° C. to 700° C. At this temperature, the microcrystals are fully developed and shaped to form the basic structure of hard carbon.

[0025] The pulverization can be carried out in a jet mill, and the particle size Dv 50 of the material after the jet milling is 3μm to 8μm. As an example, the particle size Dv 50 of the material after the pulverization can be, but is not limited to, 3μm, 3.2μm, 3.4μm, 3.5μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, 7μm, 8μm. The specific surface area of ​​the material after the pulverization is 10m 2 / g~200m 2 As an example, the specific surface area of ​​the crushed material can be, but is not limited to, 10 m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 60m 2 / g, 80m2 / g、100m 2 / g, 120m 2 / g, 140m 2 / g, 460m 2 / g, 180m 2 / g, 200m 2 / g. Controlling the particle size and specific surface area of ​​the crushed material within this range can provide a suitable pore structure for the subsequent carbonization.

[0026] The primary carbonization is carried out in an inert atmosphere, and the inert atmosphere is selected from at least one of nitrogen and argon. The temperature of the primary carbonization is 1100°C to 1600°C. In some technical schemes, the temperature of the primary carbonization is 1250°C to 1460°C. As an example, the temperature of the primary carbonization can be, but is not limited to, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, and 1600°C. The time of the primary carbonization is 0.5h to 10h. As an example, the time of the primary carbonization can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h.

[0027] In step (2), the mass ratio of hard carbon powder to starch is 1:0.05-0.5. In some technical schemes, the mass ratio of hard carbon powder to starch is 1:0.08-0.4. As an example, the mass ratio of hard carbon powder to starch can be, but is not limited to, 1:0.05, 1:0.06, 1:0.08, 1:0.1, 1:0.12, 1:0.14, 1:0.16, 1:0.18, 1:0.2, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.3, 1:0.35, 1:0.4, 1:0.5. The starch modifier includes amine organic matter and ester organic matter. The mass ratio of amine organic matter, ester organic matter and solvent is 0.2-0.5:0.5-0.8:1.0-1.5. In some technical solutions, the mass ratio of amine organic matter, ester organic matter and solvent is 0.3-0.5:0.6-0.8:1.1-1.5. In some technical solutions, the mass ratio of amine organic matter, ester organic matter and solvent is 0.3-0.4:0.6-0.7:1.1-1.4. As an example, the mass ratio of amine organic matter, ester organic matter and solvent can be, but not limited to, 0.2:0.5:1.0, 0.3:0.5:1.0, 0.4:0.5:1.0, 0.5:0.5:1.0, 0.2:0.6:1.0, 0.3:0.6:1.0, 0.4:0.6:1.0, 0.5:0.6:1.0, 0.2:0.7:1.0, 0.3:0.7:1.0, 0.4:0.7:1 .0, 0.5:0.7:1.0, 0.2:0.8:1.0, 0.3:0.8:1.0, 0.4:0.8:1.0, 0.5:0.8:1.0, 0.2:0.5:1.2, 0.3:0.5:1.2, 0.4:0.5:1.2, 0.5:0.5:1.2, 0.2:0.5:1.5, 0.3:0.5:1.5, 0.4:0.5:1.5, 0.5:0.5:1.5. Starch is selected from at least one of wheat starch, corn starch and potato starch. Amine organic matter is selected from at least one of acrylamide, ethylenediamine and aniline, ester organic matter is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate and dicyclohexylmethane diisocyanate, and solvent is selected from at least one of petroleum ether, ethyl acetate, acetone and tetrahydrofuran. Amine organic matter and ester organic matter are used as starch modifiers. Among them, amine organic matter can be grafted onto starch to enhance its swelling property, making the starch more evenly coated on the hard carbon surface. At the same time, the grafted nitrogen-containing functional groups will increase the content of pyridine and pyrrole nitrogen formed after carbonization, which can provide more electron transfer channels and more active sites, thereby increasing the conductivity and topological defects of starch-coated hard carbon negative electrode materials. At the same time, the access of nitrogen-containing functional groups can change the atomic structure of the edge or bulk phase of graphite carbon, thereby improving the battery rate performance and cycle performance.The ester organic matter of the present invention is specifically an isocyanate organic matter, whose isocyanate group can react with the hydroxyl group in starch to form a cross-linked structure, which can increase the bonding force between starch and the main skeleton of hard carbon, provide more closed-cell structures, reduce the specific surface area of ​​hard carbon, and improve the first coulombic efficiency and specific capacity.

[0028] The mass ratio of the modified solution to the mixed powder is 0.5 to 2:1. As an example, the mass ratio of the modified solution to the mixed powder can be, but is not limited to, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1. The reaction temperature is 50°C to 100°C. As an example, the reaction temperature can be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C. The reaction time is 1h to 10h. As an example, the reaction time can be, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 6.5h, 7h, 7.5h, 8h, 9h, 10h. The drying can be carried out in an oven at a temperature of 80°C to 250°C. In some technical solutions, the drying temperature is 85°C to 240°C. In some technical solutions, the drying temperature is 90°C to 188°C. As an example, the drying temperature can be, but is not limited to, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 200°C, and 250°C. The drying time is greater than 5 hours.

[0029] In step (3), the secondary carbonization is carried out in an inert atmosphere, and the inert atmosphere is selected from at least one of nitrogen and argon. The temperature of the secondary carbonization is 900°C to 1400°C. As an example, the temperature of the secondary carbonization can be, but is not limited to, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C. The insulation time of the secondary carbonization is 0.5h to 10h. As an example, the insulation time can be, but is not limited to, 0.5h, 1h, 2h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 7h, 8h, 9h, 10h. The material after secondary carbonization is first broken up in a blender and then sieved. The mesh size of the sieve used for screening is 200-400 mesh. As an example, the mesh size of the sieve used for screening can be but is not limited to 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh, 300 mesh, 325 mesh, 335 mesh, 345 mesh, 350 mesh, 360 mesh, 370 mesh, 380 mesh, 390 mesh, and 400 mesh.

[0030] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0031] Example 1

[0032] This embodiment is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0033] (1) Under a nitrogen atmosphere, 40 kg of microcrystalline cellulose was placed in a box furnace and kept at 500°C for 2 h. After the box furnace cooled to room temperature, the material was taken out and then ground in a jet mill until the particle size Dv 50 of the material was 5 μm and the specific surface area was 28.5 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1200°C for 3h under a nitrogen atmosphere to obtain hard carbon powder;

[0034] (2) 5 kg of hard carbon powder and 1 kg of corn starch were uniformly mixed to obtain a mixed powder, 0.5 kg of toluene diisocyanate and 0.2 kg of acrylamide were dissolved in 10 kg of acetone to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 50° C. for 8 h, and after the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0035] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1200° C. for 5 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0036] Example 2

[0037] This embodiment is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0038] (1) Under nitrogen atmosphere, 40 kg of rice husk was placed in a box furnace and kept at 600°C for 4 h. After the box furnace cooled to room temperature, the material was taken out and ground in a jet mill until the particle size Dv 50 was 5 μm and the specific surface area was 26.4 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1300°C for 3h under a nitrogen atmosphere to obtain hard carbon powder;

[0039] (2) 5 kg of hard carbon powder and 0.7 kg of wheat starch were uniformly mixed to obtain a mixed powder, 1 kg of dicyclohexylmethane diisocyanate and 0.3 kg of acrylamide were dissolved in 2.5 kg of petroleum ether to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 90° C. for 6 h, and after the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0040] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 900° C. for 4 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0041] Example 3

[0042] This embodiment is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0043] (1) Under nitrogen atmosphere, 40 kg of phenolic resin was placed in a box furnace and kept at 600°C for 3 h. After the box furnace cooled to room temperature, the material was taken out and then ground in a jet mill to a particle size Dv 50 of 6 μm and a specific surface area of ​​38.6 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1400℃ for 4h under nitrogen atmosphere to obtain hard carbon powder;

[0044] (2) 5 kg of hard carbon powder and 0.5 kg of potato starch were uniformly mixed to obtain a mixed powder, 1 kg of diphenylmethane diisocyanate and 0.5 kg of ethylenediamine were dissolved in 5 kg of ethyl acetate to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 85° C. for 7 h, and after the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0045] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1100° C. for 3 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0046] Example 4

[0047] This embodiment is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0048] (1) Under a nitrogen atmosphere, 40 kg of microcrystalline cellulose was placed in a box furnace and kept at 600°C for 4 h. After the box furnace cooled to room temperature, the material was taken out and then ground in a jet mill to a particle size Dv 50 of 5 μm and a specific surface area of ​​34.3 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1400℃ for 5h under nitrogen atmosphere to obtain hard carbon powder;

[0049] (2) 5 kg of hard carbon powder and 0.6 kg of corn starch were uniformly mixed to obtain a mixed powder, 1 kg of diphenylmethane diisocyanate and 0.2 kg of aniline were dissolved in 5 kg of tetrahydrofuran to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 70° C. for 6 h, and after the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0050] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1100° C. for 6 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0051] Example 5

[0052] This embodiment is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0053] (1) Under nitrogen atmosphere, 40 kg of bituminous coal was placed in a box furnace and kept at 600°C for 2 h. After the box furnace cooled to room temperature, the material was taken out and then crushed in a jet mill to a particle size Dv 50 of 5 μm and a specific surface area of ​​10.8 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1500℃ for 5h under nitrogen atmosphere to obtain hard carbon powder;

[0054] (2) 5 kg of hard carbon powder and 0.5 kg of wheat starch were uniformly mixed to obtain a mixed powder, 1 kg of toluene diisocyanate and 0.4 kg of ethylenediamine were dissolved in 2.5 kg of ethyl acetate to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 80° C. for 8 h, and after the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0055] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1000° C. for 5 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0056] Example 6

[0057] This embodiment is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0058] (1) Under a nitrogen atmosphere, 40 kg of microcrystalline cellulose was placed in a box furnace and kept at 570°C for 6 h. After the box furnace cooled to room temperature, the material was taken out and then ground in a jet mill until the particle size Dv 50 of the material was 5 μm and the specific surface area was 18.7 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1300℃ for 5h under nitrogen atmosphere to obtain hard carbon powder;

[0059] (2) 5 kg of hard carbon powder and 0.25 kg of corn starch were uniformly mixed to obtain a mixed powder, 0.5 kg of diphenylmethane diisocyanate and 0.15 kg of aniline were dissolved in 2.5 kg of acetone to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 80° C. for 8 h, and after the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0060] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1200° C. for 6 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0061] Comparative Example 1

[0062] This comparative example is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0063] (1) Under a nitrogen atmosphere, 40 kg of microcrystalline cellulose was placed in a box furnace and kept at 500°C for 2 h. After the box furnace cooled to room temperature, the material was taken out and then ground in a jet mill until the particle size Dv 50 of the material was 5 μm and the specific surface area was 31.8 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1200°C for 3h under a nitrogen atmosphere to obtain hard carbon powder;

[0064] (2) 5 kg of hard carbon powder and 1 kg of corn starch were uniformly mixed to obtain a mixed powder, 10.7 kg of acetone was added to the mixed powder, and refluxed at 50° C. for 8 h. After the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0065] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1200° C. for 5 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0066] Comparative Example 2

[0067] This comparative example is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0068] (1) Under nitrogen atmosphere, 40 kg of microcrystalline cellulose was placed in a box furnace and kept at 500°C for 2 h. After the box furnace cooled to room temperature, the material was taken out and then ground in a jet mill until the particle size Dv 50 of the material was 5 μm and the specific surface area was 29.2 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1200°C for 3h under a nitrogen atmosphere to obtain hard carbon powder;

[0069] (2) 5 kg of hard carbon powder and 1 kg of corn starch were uniformly mixed to obtain a mixed powder, 0.7 kg of toluene diisocyanate was dissolved in 10 kg of acetone to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 50 ° C for 8 hours, and after the reaction was completed, the product was placed in an oven at 85 ° C to dry to obtain a modified precursor;

[0070] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1200° C. for 5 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0071] Comparative Example 3

[0072] This comparative example is a method for preparing a starch-coated hard carbon negative electrode material, comprising the steps of:

[0073] (1) Under a nitrogen atmosphere, 40 kg of microcrystalline cellulose was placed in a box furnace and kept at 500°C for 2 h. After the box furnace cooled to room temperature, the material was taken out and then ground in a jet mill until the particle size Dv 50 of the material was 5 μm and the specific surface area was 31.0 m 2 / g, and finally put the material into a roller kiln and heat-treat it at 1200°C for 3h under a nitrogen atmosphere to obtain hard carbon powder;

[0074] (2) 5 kg of hard carbon powder and 1 kg of corn starch were uniformly mixed to obtain a mixed powder, 0.7 kg of acrylamide was dissolved in 10 kg of acetone to form a modified solution, and then the modified solution was slowly added to the mixed powder, refluxed at 50° C. for 8 h, and after the reaction was completed, the product was placed in an oven at 85° C. to dry to obtain a modified precursor;

[0075] (3) Under a nitrogen atmosphere, the modified precursor was placed in a roller kiln and heat-treated at 1200° C. for 5 h. After cooling to room temperature, the material was placed in a mixer and dispersed, and then sieved with a 325-mesh screen to obtain a starch-coated hard carbon negative electrode material.

[0076] The hard carbon powder obtained by primary carbonization and the starch-coated hard carbon negative electrode material obtained by secondary carbonization obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were respectively subjected to physical and chemical property tests, and were respectively made into half-cells for electrochemical performance tests. The half-cell preparation process and test conditions are as follows, and the test results are shown in Table 1.

[0077] Specific surface area: The nitrogen adsorption / desorption isotherms of the materials were obtained by Micromeritics ASAP 2460 analyzer, and their specific surface areas were calculated by the BET method.

[0078] Closed pore volume: calculated by CO2 adsorption / desorption pore size analysis and DFT density functional theory.

[0079] Preparation of half-cell: The hard carbon powder and starch-coated hard carbon negative electrode material in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 were respectively used as active materials, and were uniformly dispersed in deionized water with a binder carboxymethyl cellulose (CMC) at a mass ratio of 95:5 to obtain a slurry, which was then coated on a copper foil, dried in a vacuum oven at 120°C for 12 hours, and then cut into discs with a diameter of 1 cm. The surface density of the disc loaded with active materials was 0.8 to 1.0 mg / cm 2 . In a glove box with argon atmosphere (H2O<0.1ppm, O2<0.1ppm), sodium metal was used as the counter electrode, 1M NaClO4 was dissolved in 1:1 volume ratio of ethylene carbonate (EC) and diethyl carbonate (DEC) and 5% fluoroethylene carbonate (FEC) as the electrolyte, and CR2032 button cells were assembled. The electrochemical performance test was carried out on the ILJT332S constant temperature multi-channel battery test cabinet of JEIOTECH, South Korea. The charge and discharge voltage range was 0.005 to 1.5V. The button cells prepared above were tested for 0.1C first cycle charge capacity, 0.1C first cycle charge and discharge efficiency, 1C rate capacity ratio and capacity retention rate after 300 cycles at 0.5C.

[0080] Table 1 Test results of coal-based starch-coated hard carbon negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3

[0081]

[0082]

[0083]

[0084] Specifically, as shown in the test results of Table 1, it can be seen from the test results of Examples 1 to 6 and Comparative Examples 1 to 3 that the starch-coated hard carbon negative electrode material prepared by the preparation method of the present invention has more excellent electrochemical performance.

[0085] Further referring to the test results of Examples 1 to 6, the physical and chemical properties test results of the hard carbon powder obtained by the first carbonization and the starch-coated hard carbon negative electrode material obtained by the second carbonization in each embodiment are compared. It can be seen that the starch-coated hard carbon negative electrode material obtained after the modified starch coating has a reduced specific surface area, a closed-pore structure that is more conducive to sodium storage, and has a better first coulomb efficiency, specific capacity, rate performance and cycle performance. Specifically, the first reversible specific capacity at 0.1C is increased by 10mAh / g to 65mAh / g, the first coulomb efficiency is ≥90.1%, the rate capacity ratio at 1C current is increased by 16.9% to 24.1%, and the capacity retention rate after 300 cycles at 0.5C is ≥98.8%.

[0086] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that when only unmodified starch is used to coat the hard carbon powder, or when the starch modifier lacks at least one of amine organic matter and ester organic matter, the improvement of the physical and chemical properties of the resulting starch-coated hard carbon negative electrode material is relatively limited.

[0087] In summary, the present invention takes hard carbon material as the main body, and uses starch modifier to perform in-situ cross-linking modification on starch, so as to achieve uniform adhesion of starch to the hard carbon surface, improve the closed-pore structure and uniform distribution of starch-coated hard carbon negative electrode materials after carbonization, and improve the first coulombic efficiency and specific capacity. The starch modifier of the present invention includes amine organic matter and ester organic matter, wherein the amine organic matter can be grafted onto starch to improve its swelling property, so that the starch is more evenly coated on the hard carbon surface, and at the same time, the grafted nitrogen-containing functional groups will increase the content of pyridine and pyrrole nitrogen formed after carbonization, which can provide more electron transmission channels and more active sites, thereby increasing the conductivity and topological defects of starch-coated hard carbon negative electrode materials, and at the same time, the access of nitrogen-containing functional groups can change the atomic structure of the edge or bulk phase of graphite carbon, thereby improving the battery rate performance and cycle performance. The introduction of ester organic matter can form a binder with starch, increase the bonding force between starch and the main skeleton of hard carbon, provide more closed-pore structures, reduce the specific surface of hard carbon, and improve the first coulombic efficiency and specific capacity.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a starch-coated hard carbon negative electrode material, characterized in that: Includes steps: (1) Pre-carbonizing, crushing, and once carbonizing a hard carbon precursor to obtain a hard carbon powder; (2) uniformly mixing the hard carbon powder and starch to obtain a mixed powder, dissolving a starch modifier in a solvent to form a modified solution, and then reacting the modified solution with the mixed powder and drying to obtain a modified precursor, wherein the starch modifier includes an amine organic substance and an ester organic substance; (3) subjecting the modified precursor to secondary carbonization and screening.

2. The method for preparing a starch-coated hard carbon negative electrode material according to claim 1, characterized in that: The hard carbon precursor is selected from at least one of biomass, coal and resin, and the pulverization is carried out in a jet mill. The particle size Dv 50 of the pulverized material is 3 μm to 8 μm, and the specific surface area is 10 m 2 / g~200m 2 / g.

3. The method for preparing a starch-coated hard carbon negative electrode material according to claim 1, characterized in that: The pre-carbonization temperature is 400° C. to 700° C., the pre-carbonization time is 0.5 h to 10 h, the primary carbonization temperature is 1100° C. to 1600° C., and the primary carbonization insulation time is 0.5 h to 10 h.

4. The method for preparing a starch-coated hard carbon negative electrode material according to claim 1, characterized in that: The pre-carbonization, the primary carbonization and the secondary carbonization are all carried out in an inert atmosphere, and the inert atmosphere is independently selected from at least one of nitrogen and argon.

5. The method for preparing starch-coated hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the hard carbon powder to the starch is 1:0.05-0.5, the mass ratio of the amine organic matter, the ester organic matter and the solvent is 0.2-0.5:0.5-0.8:1.0-1.5, and the mass ratio of the modified solution to the mixed powder is 0.5-2:

1.

6. The method for preparing a starch-coated hard carbon negative electrode material according to claim 1, characterized in that: The starch is selected from at least one of wheat starch, corn starch and potato starch, the amine organic matter is selected from at least one of acrylamide, ethylenediamine and aniline, the ester organic matter is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate and dicyclohexylmethane diisocyanate, and the solvent is selected from at least one of petroleum ether, ethyl acetate, acetone and tetrahydrofuran.

7. The method for preparing a starch-coated hard carbon negative electrode material according to claim 1, characterized in that: The reaction temperature is 50° C. to 100° C., the reaction time is 1 h to 10 h, the drying temperature is 80° C. to 250° C., and the drying time is greater than 5 h.

8. The method for preparing starch-coated hard carbon negative electrode material according to claim 1, characterized in that: The temperature of the secondary carbonization is 900° C. to 1400° C., the insulation time of the secondary carbonization is 0.5 h to 10 h, and the mesh number used in the screening is 200 mesh to 400 mesh.

9. Starch coated hard carbon negative electrode material, characterized in that: The starch-coated hard carbon negative electrode material is prepared by the method for preparing the starch-coated hard carbon negative electrode material according to any one of claims 1 to 8.

10. A sodium ion battery comprising a positive electrode material and a negative electrode material, characterized in that: The negative electrode material is the starch-coated hard carbon negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Sodium-ion battery hard carbon negative electrode material with ultralow specific surface area and preparation method of sodium-ion battery hard carbon negative electrode material

    CN115207350A

  • Sodium ion battery negative electrode material and preparation method thereof

    CN117878318A

  • High-heat-resistance starch-based biodegradable composite material and preparation method thereof

    CN118515964A

  • Starch-based hard carbon negative electrode material and preparation method and application thereof

    CN119008253A

  • Negative electrode material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery using it

    JP2004311237A